ILBES: An Intergenerational Learning Approach for Social Inclusion in Blended Environments and Spaces - Andrea Diaz Mattei; Gabriel Rissola (Pensa MultiMedia, 2012)
Public libraries, educational, cultural or welfare centres, and other public spaces where digital services are embedded, hereby referred as Blended Environments and Spaces (BES), have become an important provider of free, public access to ICT, internet and learning environments for sociallydisadvantaged target groups. They are a reference point for new technologies, non-formal learning, people empowerment and social integration. The clientele of BES largely includes seniors and elders who are digitally illiterate, as well as youngsters volunteering as adult trainers on the basis of their own digital competences. At the same time, the current economic downturn is pushing the job-inexperienced youngsters to look for help at these and other centres with social vocation due to the reduced employment opportunities they found. The Intergenerational Learning in Blended Environments and Spaces (ILBES) methodology was developed as part of eScouts, an EC-funded project. It is inspired in two proven learning methodologies (Community-Service Learning and Participatory and Appreciative Action and Reflection) which are combined for the first time in the design of an intergenerational learning circle that facilitates the socio-digital inclusion of seniors and the entrance of youth to the labour market and adult life, while improving solidarity between generations and local community cohesion.